Multiple myeloma: MR patterns of response to treatment - Moulopoulos, L.A.; Dimopoulos, M.A.; Alexanian, R.; Leeds, N.E.; Libshitz, H.I. (Radiology, 1994)
PURPOSE: To assess changes in the magnetic resonance (MR) appearance of the spine in patients with multiple myeloma who responded to chemotherapy. MATERIALS AND METHODS: Twenty patients with multiple myeloma underwent MR imaging of the spine before and after chemotherapy. Sagittal T1-weighted images were obtained before and after administration of contrast material. MR patterns of marrow involvement before treatment were classified as focal, diffuse, or variegated. The changes seen on MR images after treatment were analyzed and correlated with the clinical response as defined with standard criteria. RESULTS: Patterns of complete response included resolution of marrow abnormality or persistent abnormality without enhancement or with peripheral rim enhancement. Conversion of a diffuse to a variegated or focal pattern and a decrease in the amount of marrow abnormality with persistent enhancement were observed in patients who showed a partial response. Ten patients sustained new or progressive compression fractures after successful therapy. CONCLUSION: Recognition of spinal MR patterns of response to treatment supported the occurrence of remission in patients with multiple myeloma. MR findings may help clarify response to therapy in patients with equivocal clinical changes or nonsecretory myeloma.
Keywords: Bone marrow, MR; Bone marrow, neoplasms; myeloma; Spine, MR